Methodology for optimizing business processes based on the parameters of differentiation - E. Plakhin, Andrey (2021)
The purpose of this study was to develop and test a methodological approach to optimizing the business processes of the leather industry company of the Republic of Iraq on the basis of a series of sequential steps, including both assessing the individual parameters of the differentiation of the competitive strategy and identifying problem areas for further setting up business processes. The results of the study are expressed in the form of developing an author's algorithm for identifying competitiveness parameters in accordance with the type of competitive strategy, as well as in the form of developing a matrix for determining a competitive strategy. By summarizing the scientific research, the authors presented for scientific consideration the main parameters of differentiation of the business model of leather products, as well as the analytical scheme of cost analysis in relation to their research object. The methodology presented in this work can be used both to build an effective system of state support measures, and can be used in the educational process of higher educational institutions as didactic and practical material.